Information and communication technology : third IFIP TC 5/8 International Conference, ICT-EurAsia 2015, and 9th IFIP WG 8.9 Working Conference, CONFENIS 2015, held as part of WCC 2015, Daejeon, Korea, October 4-7, 2015, Proceedings /: third IFIP TC 5/8 International Conference, ICT-EurAsia 2015, and 9th IFIP WG 8.9 Working Conference, CONFENIS 2015, held as part of WCC 2015, Daejeon, Korea, October 4-7, 2015, Proceedings. (2015) - Unknown
No abstract available